Conditional Singlet Oxygen Generation through a Bioorthogonal DNA‐targeted Tetrazine Reaction. Issue 37 (12th August 2019) - Linden, Greta; Zhang, Lei; Pieck, Fabian; Linne, Uwe; Kosenkov, Dmitri; Tonner, Ralf; Vázquez, Olalla
Abstract: We report the use of bioorthogonal reactions as an original strategy in photodynamic therapy to achieve conditional phototoxicity and specific subcellular localization simultaneously. Our novel halogenated BODIPY‐tetrazine probes only become efficient photosensitizers (ΦΔ ≈0.50) through an intracellular inverse‐electron‐demand Diels–Alder reaction with a suitable dienophile. Ab initio computations reveal an activation‐dependent change in decay channels that controls 1 O2 generation. Our bioorthogonal approach also enables spatial control. As a proof‐of‐concept, we demonstrate the feasibility of the selective activation of our dormant photosensitizer in cellular nuclei, causing cancer cell death upon irradiation. Thus, our dual biorthogonal, activatable photosensitizers open new venues to combat current limitations of photodynamic therapy. Abstract : Two birds with one stone : Biorthogonal, activatable, halogenated BODIPY‐tetrazine photosensitizers have been developed that allow both organelle‐specific localization and conditional singlet oxygen production simultaneously.